Collaborative Systems Thinking Culture: A Path to Success for Complex Projects. Issue 1 (26th September 2022) - Bouyaud, Mickael; Davila‐Rendon, Natalie; Deng, Alex; Duprez, Jean; Fraga, Anabel; John, Leema; Noguchi, Ryan; Palmer, Erika; Patel, Jay; Romero, Maria; Wolfgang, Raymond; Wozniak, Michael
Abstract: The world is filled with hard and complex problems, oftentimes requiring involved solutions. In large organizations attempting to solve these types of problems, a mindset shift and key candidate methodologies centered on collaborative systems thinking culture (CSTC) can assist significantly. The paper explores the state of the practice, change involved with implementing systems thinking, impacts of a collaborative approach within an organization, as well as the seven phases that a reader can introduce into their organization to realize some of the benefits. The same approach was used to create this paper under collective authorship from Cohort 6 of the INCOSE Technical Leadership Institute (TLI); an international group of individuals collaborating exclusively through virtual platforms. From writing papers to executing large technical programs, the CSTC approach will prepare technical teams for tackling challenging problems in an inclusive way with the intent to finish projects on time while also cultivating healthy systems engineering habits and practices. This lessens the reliance on corporate engineering procedures to drive collaborative behavior by fiat. Finally, blending CSTC into the fabric and culture of an organization is emphasized as being needed for the full benefit. That benefit includes saving programs by moving to a CSTC.